(untitled) (Contemporary Journal of Social Science Review, 2025)
This mixed-methods study investigates the impact of social networking platforms (SNPs) on English language proficiency and academic achievement among undergraduate students at the University of Punjab in Lahore. The total number of respondents (n = 315 undergraduate students) from various faculties was taken as a sample. Quantitative data was collected from (n = 300) using a self-developed structured questionnaire covering demographics, SNPs usage, self-assessed English proficiency, and academic achievement (CGPA). At the same time, qualitative insights were obtained from (n = 15) through semi-structured interviews using a convenience sampling technique. The study investigates usage patterns, linguistic impacts, and academic implications. The findings reveal a modest connection in which moderate and academically inclined SNPs consumption correlates positively with English language acquisition and overall academic attainment. However, excessive or non-academic use hurts English language proficiency and academic performance. The study concludes with educational implications and guidelines for effectively integrating SNPs into academic and linguistic development programs.